High-strength PEO-based solid-state electrolyte and preparation method and application thereof
Patent Information
- Application Number
- CN202610784882.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-06-02
- Publication Date
- 2026-09-22
AI Technical Summary
[0004]本发明所要解决的技术问题在于提供一种PEO基固态电解质,通过改性二氧化硅的添加不仅可以提高PEO基固态电解质的机械强度,还解决了直接添加二氧化硅存在的离子电导率降低、界面相容性差等问题
[0024]本发明的有益效果是:本发明在二氧化硅表面通过化学反应引入苯基丙烯酸酯聚合物链,不仅能改变二氧化硅的表面性质,提高其在PEO基固态电解质中的分散性和相容性,还可实现PEO基固态电解质的机械强度与离子电导率的协同优化,从而提升电池的安全性以及充放电性能。
Abstract
Description
Technical Field
[0001] This invention relates to the field of solid electrolyte technology, specifically to a high-strength PEO-based solid electrolyte, its preparation method, and its application. Background Technology
[0002] Polymer solid electrolytes are solid ion conductor materials composed of polymer matrices (such as polyethylene oxide, abbreviated as PEO) and electrolyte salts such as lithium salts. They have advantages such as high safety, good flexibility, easy processing into films, and good contact with electrode interfaces.
[0003] PEO-based solid electrolytes are among the most widely researched and maturely applied polymer solid electrolytes, possessing unique advantages but also exhibiting significant limitations, including low room-temperature ionic conductivity, poor oxidative stability, insufficient mechanical strength, limited thermal stability, and a relatively low lithium-ion transference number. The insufficient mechanical strength stems from PEO's semi-crystalline state at room temperature. While the crystalline regions provide some rigidity, the excessive flexibility of the amorphous regions leads to susceptibility to plastic deformation, resulting in lower tensile strength and modulus. The PEO backbone, composed of repeating -CH2-CH2-O- units, has a low rotational energy barrier for ether bonds, giving the molecular chain high flexibility and fluidity, but also weakening the material's resistance to external forces. Summary of the Invention
[0004] The technical problem to be solved by the present invention is to provide a PEO-based solid electrolyte. By adding modified silica, not only can the mechanical strength of the PEO-based solid electrolyte be improved, but the problems of reduced ionic conductivity and poor interfacial compatibility caused by directly adding silica are also solved.
[0005] The technical problem to be solved by this invention is achieved by the following technical solution:
[0006] One of the objectives of this invention is to provide a PEO-based solid electrolyte, comprising PEO, lithium salt, and modified silicon dioxide.
[0007] Furthermore, the modified silica accounts for 5-10% of the mass of the PEO-based solid electrolyte.
[0008] Furthermore, the modified silica is prepared by reacting silica and 2,4,6-tribromophenyl acrylate with an acid-binding agent and an initiator.
[0009] Furthermore, the acid-binding agent includes, but is not limited to, one or more of triethylamine, pyridine, and N,N-diisopropylethylamine.
[0010] Furthermore, the initiator includes, but is not limited to, one or more of dicumyl peroxide, tert-butyl peroxide, and cumyl hydroperoxide.
[0011] Furthermore, the mass ratio of silica to 2,4,6-tribromophenyl acrylate is 10:(5~10); the molar ratio of acid-binding agent to 2,4,6-tribromophenyl acrylate is (1~2):1; and the amount of initiator is 0.1~1% of the mass of 2,4,6-tribromophenyl acrylate.
[0012] In some specific embodiments, the modified silica is prepared by first adding silica, 2,4,6-tribromophenyl acrylate and an acid-binding agent to toluene for a substitution reaction, then adding an initiator for a polymerization reaction, and finally distilling under reduced pressure after the reaction is completed, washing the residue with water and drying it under vacuum to obtain modified silica.
[0013] Furthermore, the molecular weight of the PEO is 200,000 to 600,000.
[0014] Furthermore, the lithium salt includes, but is not limited to, one or more of lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), lithium bis(fluorosulfonyl)imide (LiFSI), lithium difluorooxalateborate (LiDFOB), lithium hexafluorophosphate (LiPF6), and lithium tetrafluoroborate (LiBF4).
[0015] Furthermore, the lithium salt accounts for 10-40% of the mass of the PEO-based solid electrolyte.
[0016] Furthermore, the PEO-based solid electrolyte further includes perfluoronickel(II). Preferably, the perfluoronickel(II) accounts for 1-3% of the mass of the PEO-based solid electrolyte.
[0017] The second objective of this invention is to provide a method for preparing the PEO-based solid electrolyte, wherein PEO, lithium salt and modified silica are added to a solvent, mixed evenly and then cast into a mold, and the solvent is removed by drying to obtain the PEO-based solid electrolyte.
[0018] The third objective of this invention is to provide a method for preparing the PEO-based solid electrolyte, wherein PEO, lithium salt, modified silica and perfluorophthalocyanine nickel(II) are added to a solvent, mixed evenly, and then cast into a mold. The solvent is removed by drying to obtain the PEO-based solid electrolyte.
[0019] Furthermore, the solvent includes, but is not limited to, one or more of acetonitrile, acetone, tetrahydrofuran, N,N-dimethylformamide, and N-methylpyrrolidone. A suitable solvent is selected based on the solubility of PEO and lithium salts.
[0020] Furthermore, the drying process is vacuum drying. The solvent is removed by vacuum drying, and the film is solidified.
[0021] PEO-based solid electrolyte membranes of different thicknesses can be obtained by solution casting, and ultra-thin PEO-based solid electrolyte membranes can also be obtained by hot pressing to meet different application requirements.
[0022] The fourth objective of this invention is to provide the application of the PEO-based solid electrolyte in solid-state lithium batteries.
[0023] The fifth objective of this invention is to provide a solid-state lithium battery, comprising a positive electrode, a negative electrode, and the PEO-based solid electrolyte.
[0024] The beneficial effects of this invention are: by introducing phenyl acrylate polymer chains onto the surface of silica through a chemical reaction, this invention can not only change the surface properties of silica and improve its dispersibility and compatibility in PEO-based solid electrolytes, but also achieve synergistic optimization of the mechanical strength and ionic conductivity of PEO-based solid electrolytes, thereby improving the safety and charge / discharge performance of the battery. Detailed Implementation
[0025] To make the technical means, creative features, objectives and effects of this invention easier to understand, the invention will be further described below with reference to specific embodiments.
[0026] The silica used in the following examples and comparative examples was purchased from Wuhan Kemic Biomedical Technology Co., Ltd., and the particle size was 50~100 nm.
[0027] Example 1
[0028] Preparation of modified silica: 10 g of silica, 10 g of 2,4,6-tribromophenyl acrylate, and triethylamine were added to 500 mL of toluene. The molar ratio of triethylamine to 2,4,6-tribromophenyl acrylate was 1.5:1. The mixture was refluxed for 3 h. Then, cumene hydroperoxide was added, with the amount of cumene hydroperoxide being 0.5% of the mass of 2,4,6-tribromophenyl acrylate. The mixture was refluxed for another 3 h. After the reaction was completed, the mixture was distilled under reduced pressure. The residue was washed with water, dried under vacuum at 60 °C, and ground to obtain modified silica with a particle size of 50-100 nm.
[0029] Preparation of PEO-based solid electrolyte: 7.5 g PEO (molecular weight of 200,000), 2 g LiTFSI and 0.5 g modified silica were added to 250 mL acetonitrile, mixed evenly and then cast into a mold. The mixture was then vacuum dried at 50 °C to obtain PEO-based solid electrolyte.
[0030] Example 2
[0031] Preparation of modified silica: 10 g of silica, 5 g of 2,4,6-tribromophenyl acrylate and pyridine were added to 500 mL of toluene. The molar ratio of pyridine to 2,4,6-tribromophenyl acrylate was 1:1. The mixture was refluxed for 3 h. Then, dicumyl peroxide was added. The amount of dicumyl peroxide was 0.35% of the mass of 2,4,6-tribromophenyl acrylate. The mixture was refluxed for another 3 h. After the reaction was completed, the mixture was distilled under reduced pressure. The residue was washed with water, dried under vacuum at 60 °C, and ground to obtain modified silica with a particle size of 50~100 nm.
[0032] Preparation of PEO-based solid electrolyte: 7 g PEO (molecular weight 400,000), 2.5 g LiTFSI and 0.5 g modified silica were added to 250 mL N,N-dimethylformamide, mixed evenly and then cast into a mold. The mixture was then vacuum dried at 70 °C to obtain PEO-based solid electrolyte.
[0033] Example 3
[0034] Preparation of modified silica: 10 g of silica, 8 g of 2,4,6-tribromophenylacrylate and N,N-diisopropylethylamine were added to 500 mL of toluene. The molar ratio of N,N-diisopropylethylamine to 2,4,6-tribromophenylacrylate was 2:1. The mixture was refluxed for 3 h. Then, tert-butyl peroxide was added, with the amount of tert-butyl peroxide being 1% of the mass of 2,4,6-tribromophenylacrylate. The mixture was refluxed for another 3 h. After the reaction was completed, the mixture was distilled under reduced pressure. The residue was washed with water, dried under vacuum at 60 °C, and ground to obtain modified silica with a particle size of 50-100 nm.
[0035] Preparation of PEO-based solid electrolyte: 6 g PEO (molecular weight of 600,000), 3.2 g LiFSI and 0.8 g modified silica were added to 250 mL acetonitrile, mixed evenly and then cast into a mold. The mixture was then vacuum dried at 55 °C to obtain PEO-based solid electrolyte.
[0036] Example 4
[0037] Preparation of modified silica: 10 g of silica, 9 g of 2,4,6-tribromophenyl acrylate and triethylamine were added to 500 mL of toluene. The molar ratio of triethylamine to 2,4,6-tribromophenyl acrylate was 2:1. The mixture was refluxed for 3 h. Then, dicumyl peroxide was added, with the amount of dicumyl peroxide being 0.5% of the mass of 2,4,6-tribromophenyl acrylate. The mixture was refluxed for another 3 h. After the reaction was completed, the mixture was distilled under reduced pressure. The residue was washed with water, dried under vacuum at 60 °C, and ground to obtain modified silica with a particle size of 50-100 nm.
[0038] Preparation of PEO-based solid electrolyte: 6 g PEO (molecular weight 600,000), 3 g LiFSI and 1 g modified silica were added to 250 mL N-methylpyrrolidone, mixed evenly and then cast into a mold. The mixture was then vacuum dried at 70 °C to obtain PEO-based solid electrolyte.
[0039] Example 5
[0040] Preparation of modified silica: 10 g of silica, 10 g of 2,4,6-tribromophenyl acrylate, and N,N-diisopropylethylamine were added to 500 mL of toluene. The molar ratio of N,N-diisopropylethylamine to 2,4,6-tribromophenyl acrylate was 1.2:1. The mixture was refluxed for 3 h. Then, cumene hydroperoxide was added, with the amount of cumene hydroperoxide being 0.8% of the mass of 2,4,6-tribromophenyl acrylate. The mixture was refluxed for another 3 h. After the reaction was completed, the mixture was distilled under reduced pressure. The residue was washed with water, dried under vacuum at 60 °C, and ground to obtain modified silica with a particle size of 50-100 nm.
[0041] Preparation of PEO-based solid electrolyte: 6 g PEO (molecular weight of 600,000), 3 g LiTFSI and 1 g modified silica were added to 250 mL acetonitrile, mixed evenly and then cast into a mold. The mixture was then vacuum dried at 50 °C to obtain PEO-based solid electrolyte.
[0042] Example 6
[0043] Preparation of modified silica: 10 g of silica, 6 g of 2,4,6-tribromophenyl acrylate and triethylamine were added to 500 mL of toluene. The molar ratio of triethylamine to 2,4,6-tribromophenyl acrylate was 1.8:1. The mixture was refluxed for 3 h. Then, dicumyl peroxide was added, with the amount of dicumyl peroxide being 0.5% of the mass of 2,4,6-tribromophenyl acrylate. The mixture was refluxed for another 3 h. After the reaction was completed, the mixture was distilled under reduced pressure. The residue was washed with water, dried under vacuum at 60 °C, and ground to obtain modified silica with a particle size of 50~100 nm.
[0044] Preparation of PEO-based solid electrolyte: 5 g PEO (molecular weight of 600,000), 4 g LiTFSI and 1 g modified silica were added to 250 mL acetonitrile, mixed evenly and then cast into a mold. The mixture was then vacuum dried at 55 °C to obtain PEO-based solid electrolyte.
[0045] Comparative Example 1
[0046] Modified silica and PEO-based solid electrolytes were prepared according to the method in Example 5, except that 2,4,6-tribromophenyl acrylate was replaced with allyl 4-bromobutyrate.
[0047] Preparation of modified silica: 10 g of silica, 10 g of allyl 4-bromobutyrate, and N,N-diisopropylethylamine were added to 500 mL of toluene. The molar ratio of N,N-diisopropylethylamine to allyl 4-bromobutyrate was 1.2:1. The mixture was refluxed for 3 h. Then, cumene hydroperoxide was added, with the amount of cumene hydroperoxide being 0.8% of the mass of allyl 4-bromobutyrate. The mixture was refluxed for another 3 h. After the reaction was completed, the mixture was distilled under reduced pressure. The residue was washed with water, dried under vacuum at 60 °C, and ground to obtain modified silica with a particle size of 50-100 nm.
[0048] Preparation of PEO-based solid electrolyte: 6 g PEO (molecular weight of 600,000), 3 g LiTFSI and 1 g modified silica were added to 250 mL acetonitrile, mixed evenly and then cast into a mold. The mixture was then vacuum dried at 50 °C to obtain PEO-based solid electrolyte.
[0049] Comparative Example 2
[0050] Modified silica and PEO-based solid electrolytes were prepared according to the method in Example 5, except that 2,4,6-tribromophenyl acrylate was replaced with (E)-3-bromoacrylate methyl ester.
[0051] Preparation of modified silica: 10 g of silica, 10 g of (E)-3-bromoacrylate and N,N-diisopropylethylamine were added to 500 mL of toluene. The molar ratio of N,N-diisopropylethylamine to (E)-3-bromoacrylate was 1.2:1. The mixture was refluxed for 3 h. Then, cumene hydroperoxide was added, with the amount of cumene hydroperoxide being 0.8% of the mass of (E)-3-bromoacrylate. The mixture was refluxed for another 3 h. After the reaction was completed, the mixture was distilled under reduced pressure. The residue was washed with water, dried under vacuum at 60 °C, and ground to obtain modified silica with a particle size of 50~100 nm.
[0052] Preparation of PEO-based solid electrolyte: 6 g PEO (molecular weight of 600,000), 3 g LiTFSI and 1 g modified silica were added to 250 mL acetonitrile, mixed evenly and then cast into a mold. The mixture was then vacuum dried at 50 °C to obtain PEO-based solid electrolyte.
[0053] Comparative Example 3
[0054] Modified silica and PEO-based solid electrolytes were prepared according to the method in Example 5, except that 2,4,6-tribromophenyl acrylate was replaced with silane coupling agent A171.
[0055] Preparation of modified silica: 10 g of silica, 10 g of silane coupling agent A171 and N,N-diisopropylethylamine were added to 500 mL of toluene. The molar ratio of N,N-diisopropylethylamine to silane coupling agent A171 was 1.2:1. The mixture was refluxed for 3 h. Then, cumene hydrogen peroxide was added, with the amount of cumene hydrogen peroxide being 0.8% of the mass of silane coupling agent A171. The mixture was refluxed for another 3 h. After the reaction was completed, the mixture was distilled under reduced pressure. The residue was washed with water, dried under vacuum at 60 °C, and ground to obtain modified silica with a particle size of 50~100 nm.
[0056] Preparation of PEO-based solid electrolyte: 6 g PEO (molecular weight of 600,000), 3 g LiTFSI and 1 g modified silica were added to 250 mL acetonitrile, mixed evenly and then cast into a mold. The mixture was then vacuum dried at 50 °C to obtain PEO-based solid electrolyte.
[0057] Comparative Example 4
[0058] PEO-based solid electrolytes were prepared according to the method in Example 5, except that the silica was not modified.
[0059] Preparation of PEO-based solid electrolyte: 6 g PEO (molecular weight of 600,000), 3 g LiTFSI and 1 g silicon dioxide were added to 250 mL acetonitrile, mixed evenly and then cast into a mold. The mixture was then vacuum dried at 50 °C to obtain PEO-based solid electrolyte.
[0060] Example 7
[0061] Modified silica and PEO-based solid electrolytes were prepared according to the method in Example 5, except that perfluorophthalocyanine nickel(II) was also added.
[0062] Preparation of modified silica: 10 g of silica, 10 g of 2,4,6-tribromophenyl acrylate, and N,N-diisopropylethylamine were added to 500 mL of toluene. The molar ratio of N,N-diisopropylethylamine to 2,4,6-tribromophenyl acrylate was 1.2:1. The mixture was refluxed for 3 h. Then, cumene hydroperoxide was added, with the amount of cumene hydroperoxide being 0.8% of the mass of 2,4,6-tribromophenyl acrylate. The mixture was refluxed for another 3 h. After the reaction was completed, the mixture was distilled under reduced pressure. The residue was washed with water, dried under vacuum at 60 °C, and ground to obtain modified silica with a particle size of 50-100 nm.
[0063] Preparation of PEO-based solid electrolyte: 5.9 g PEO (molecular weight of 600,000), 3 g LiTFSI, 1 g modified silica and 0.1 g perfluorophthalocyanine nickel(II) were added to 250 mL acetonitrile. After mixing evenly, the mixture was cast into a mold and dried under vacuum at 50 °C to obtain PEO-based solid electrolyte.
[0064] Example 8
[0065] Modified silica and PEO-based solid electrolytes were prepared according to the method in Example 5, except that perfluorophthalocyanine nickel(II) was also added.
[0066] Preparation of modified silica: 10 g of silica, 10 g of 2,4,6-tribromophenyl acrylate, and N,N-diisopropylethylamine were added to 500 mL of toluene. The molar ratio of N,N-diisopropylethylamine to 2,4,6-tribromophenyl acrylate was 1.2:1. The mixture was refluxed for 3 h. Then, cumene hydroperoxide was added, with the amount of cumene hydroperoxide being 0.8% of the mass of 2,4,6-tribromophenyl acrylate. The mixture was refluxed for another 3 h. After the reaction was completed, the mixture was distilled under reduced pressure. The residue was washed with water, dried under vacuum at 60 °C, and ground to obtain modified silica with a particle size of 50-100 nm.
[0067] Preparation of PEO-based solid electrolyte: 5.7 g PEO (molecular weight of 600,000), 3 g LiTFSI, 1 g modified silica and 0.3 g perfluorophthalocyanine nickel(II) were added to 250 mL acetonitrile. After mixing evenly, the mixture was cast into a mold and dried under vacuum at 50 °C to obtain PEO-based solid electrolyte.
[0068] The PEO-based solid electrolytes prepared in Examples 1-8 and Comparative Examples 1-4 were cut into specimens with dimensions of 25 mm × 5 mm × 100 μm using a universal testing machine and then subjected to tensile strength tests. The temperature was 25℃ and the tensile speed was 10 mm / min. The average value of the results of 5 tests is shown in Table 1.
[0069] The PEO-based solid electrolytes with a thickness of 100 μm prepared in Examples 1-8 and Comparative Examples 1-4 were cut into discs with a diameter of 19 mm. Stainless steel sheets (11 mm in diameter and 1 mm in thickness) were used as the positive electrode, and lithium sheets (11 mm in diameter and 0.5 mm in thickness) were used as the negative electrode. Stainless steel / solid electrolyte / lithium sheet coin cells were assembled in an argon-filled glove box. The linear voltammetric scan (LSV) curves of the cells were tested using a Shanghai Chenhua 660E electrochemical workstation. The average value of five test results is shown in Table 1. Test conditions: temperature 25℃, voltage 0-6 V, scan rate 0.1 mV / s.
[0070] Table 1
[0071] Example 1 <![CDATA[3.89×10 -5 ]]> 2.21 Example 2 <![CDATA[4.15×10 -5 ]]> 2.17 Example 3 <![CDATA[6.08×10 -5 ]]> 2.25 Example 4 <![CDATA[5.72×10 -5 ]]> 2.31 Example 5 <![CDATA[5.97×10 -5 ]]> 2.38 Example 6 <![CDATA[4.86×10 -5 ]]> 2.27 Example 7 <![CDATA[6.53×10 -5 ]]> 2.34 Example 8 <![CDATA[7.29×10 -5 ]]> 2.30 Comparative Example 1 <![CDATA[2.08×10 -5 ]]> 1.06 Comparative Example 2 <![CDATA[2.27×10 -5 ]]> 1.13 Comparative Example 3 <![CDATA[2.54×10 -5 ]]> 1.52 Comparative Example 4 <![CDATA[3.16×10 -5 ]]> 0.97
[0072] As shown in Table 1, the present invention can significantly improve the tensile strength of PEO-based solid electrolytes by preparing and adding modified silica, and also enable PEO-based solid electrolytes to have high room temperature ionic conductivity.
[0073] The foregoing has shown and described the basic principles, main features, and advantages of the present invention. Those skilled in the art should understand that the present invention is not limited to the above embodiments. The embodiments and descriptions in the specification are merely illustrative of the principles of the invention. Various changes and modifications can be made to the invention without departing from its spirit and scope, and all such changes and modifications fall within the scope of the present invention as claimed. The scope of protection of this invention is defined by the appended claims and their equivalents.
Claims
1. A PEO-based solid electrolyte, characterized in that: The PEO-based solid electrolyte comprises PEO, lithium salt, and modified silicon dioxide.
2. The PEO-based solid electrolyte according to claim 1, characterized in that: The modified silica accounts for 5-10% of the mass of the PEO-based solid electrolyte.
3. The PEO-based solid electrolyte according to claim 1, characterized in that: The modified silica is prepared by reacting silica and 2,4,6-tribromophenyl acrylate under the action of an acid-binding agent and an initiator; Preferably, the acid-binding agent is one or more of triethylamine, pyridine, and N,N-diisopropylethylamine; Preferably, the initiator is one or more of dicumyl peroxide, tert-butyl peroxide, and cumyl hydroperoxide. Preferably, the mass ratio of silica to 2,4,6-tribromophenyl acrylate is 10:(5~10); the molar ratio of acid-binding agent to 2,4,6-tribromophenyl acrylate is (1~2):1; and the amount of initiator is 0.1~1% of the mass of 2,4,6-tribromophenyl acrylate.
4. The PEO-based solid electrolyte according to claim 3, characterized in that: The modified silica is prepared by first adding silica, 2,4,6-tribromophenyl acrylate and an acid-binding agent to toluene for a substitution reaction, then adding an initiator for a polymerization reaction, and finally distilling under reduced pressure after the reaction is completed. The residue is washed with water and dried under vacuum to obtain modified silica.
5. The PEO-based solid electrolyte according to claim 1, characterized in that: The molecular weight of the PEO is 200,000 to 600,000.
6. The PEO-based solid electrolyte according to claim 1, characterized in that: The lithium salt is selected from one or more of lithium bis(trifluoromethanesulfonyl)imide, lithium bis(fluorosulfonyl)imide, lithium difluorooxalateborate, lithium hexafluorophosphate, and lithium tetrafluoroborate.
7. The PEO-based solid electrolyte according to claim 1, characterized in that: The lithium salt accounts for 10-40% of the mass of the PEO-based solid electrolyte.
8. The method for preparing the PEO-based solid electrolyte according to any one of claims 1 to 7, characterized in that: PEO, lithium salt and modified silica are added to the solvent, mixed evenly and then cast into a mold. The solvent is removed by drying to obtain PEO-based solid electrolyte.
9. The application of the PEO-based solid electrolyte according to any one of claims 1 to 7 in solid-state lithium batteries.
10. A solid-state lithium battery, comprising a positive electrode, a negative electrode, and a PEO-based solid electrolyte as described in any one of claims 1 to 7.